2020
DOI: 10.3329/bjms.v19i4.46617
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the effect of the gender factor on university students’ physical activity level

Abstract: Objective: Scientific research provide information concerning an insufficient level of physical activity of young people. This study was conducted to determine the levels of physical activity among university students. Materials and Methods: In 2014-2015 academic year, 510 students voluntarily participated in this study. To obtain data, the Personal Information Form and to determine the levels of physical activity. International Physical Activity Questionnaire (IPAQ) were used. Results and Discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…In terms of PAL, significant associations were found between both sexes ( p < 0.001). The results showed that men were more physically active than women (14.4 vs. 9.1) and women were more inactive than men (15.9% vs. 12.6%), which is in line with previous research on the amount of PA performed by men and women in different age ranges [ 22 , 46 , 47 , 48 , 49 ]. In terms of who were the most active subjects, men again scored higher than women (16.1% vs. 8.8%), similar to previous studies [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of PAL, significant associations were found between both sexes ( p < 0.001). The results showed that men were more physically active than women (14.4 vs. 9.1) and women were more inactive than men (15.9% vs. 12.6%), which is in line with previous research on the amount of PA performed by men and women in different age ranges [ 22 , 46 , 47 , 48 , 49 ]. In terms of who were the most active subjects, men again scored higher than women (16.1% vs. 8.8%), similar to previous studies [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with the results of a large questionnaire survey on the extent of weekly physical activity of the Czech population in 2005-2009, which showed that men had more than 6000 MET min/week and women more than 5000 MET min/week [29]. Our results are not entirely consistent with those of the study by Dikmen et al [30], where the authors reported that only 18% of university students (510 students, 80% women and 20% men) who filled in the IPAQ had sufficient physical activity (6% women and 12% men; the fact that men that are physically more active than women was confirmed also in our study). In the discussion, the authors then referred to studies with results similar to theirs.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with the results of a large questionnaire survey on the extent of weekly physical activity of the Czech population in 2005-2009, which showed that men have more than 6000 MET min/week and women more than 5000 MET min/week [24]. Our results are not entirely consistent with those of the study by Dikmen et al [25], where the authors reported that only 18% of university students (510 students, 80% women and 20% men) who participated in the IPAQ had su cient physical activity (6% women and 12% men). It can be considered identical, that men are physically more active than women.…”
Section: Discussionsupporting
confidence: 90%